Collaborative Pathways to Cybersecurity Excellence: Insights from Industry and Academia in the Southeastern US - Humayun Zafar; Carole L. Hollingsworth; Tridib Bandyopadhyay; Adriane B. Randolph (Journal of Cybersecurity Education, Research & Practice)
This research article examines conversations happening between cybersecurity academics and industry leaders with a goal to improve the development of cybersecurity professionals. We specifically focus on efforts in the Southeast region of the United States. The discussion features insights from a panel consisting of an academic cybersecurity researcher, a Chief Information Officer (CIO) of a leading technology company with over 1,000 employees, and a CIO of a financial services firm, which employs over 3,000 people. The discussion sheds light on the challenges and opportunities involved in aligning cybersecurity programs with industry requirements. This article explores strategies for academia and businesses to work together in shaping cybersecurity education addressing issues like the skills gap and lack of practical experience among recent graduates. It emphasizes the challenges faced by technology and financial sectors when hiring cybersecurity experts and suggests integrated solutions such as co-developed curriculum and experiential learning initiatives. Through a series of brief case studies, this article then examines the effectiveness of such integrated solutions. This collection of perspectives provides a roadmap for strengthening collaboration between institutions and industry—an essential step towards building a strong, adaptable workforce in the field of cybersecurity.